Peran Wanita dalam Pandangan Politik: Analisis Ayat-Ayat tentang Peran Wanita dalam Q.S. At-Taubah: 71 dan Q.S An-Nisa 34 - Inggria, Annisa; Priwulan, Marpria; Siregar, Armaida; B.Bara, Sarah Kumala; Siregar, Nina Sari; Harahap, Mardian Idris (VISA: Journal of Vision and Ideas, 2024)
This article was written with the aim of analyzing the verses of the Koran relating to leadership and understanding the role of women according to Q.S. An-Nisa verse 34. In this study the focus that will be discussed is the history of women in the world of leadership regarding how leadership roles in the political field are not only filled by men but can also be carried out by women. Writing this article uses qualitative methods and techniques in collecting data with a library-based approach or library research, namely explaining the material that will be discussed by collecting several library sources, both primary and secondary. Primary literature sources referred to are books that discuss women's role participation in politics and secondary literature sources used are journals that are relevant to key discussions about the role of women in leadership both according to the view of the Al-Qur'an and also according to political views. . The findings that the author got from writing this article are first, in the history of Islamic civilization there has been a role for women in the world of political leadership such as Queen Bilqis from Negri Saba' and Syajaratud Dur who was the sultan of Egypt. Second, based on the analysis of Surah At-Taubah verse 71, women can also have the same role in the field of leadership, not just men. Here the two can work together together.